Kearifan Abdurrahman Wahid (Gus Dur) Terhadap Budaya Lokal Indonesia Ucapan “Assalamualaikum” - moh mustaqim (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
He has taken the time to think about Islamic values, nationality, local culture, and play an important role in the development of Islam, the Indonesian nation. He maintains religious traditions, ethnicity, including cross-groups, and politics. Gus Dur is a thinker who often gets about from other people. One of his remarks as the implementation of the idea of ​​